2009
DOI: 10.1007/s12033-008-9131-y
|View full text |Cite
|
Sign up to set email alerts
|

DSN Depletion is a Simple Method to Remove Selected Transcripts from cDNA Populations

Abstract: A novel DSN-depletion method allows elimination of selected sequences from full-length-enriched cDNA libraries. Depleted cDNA can be applied for subsequent EST sequencing, expression cloning, and functional screening approaches. The method employs specific features of the kamchatka crab duplex-specific nuclease (DSN). This thermostable enzyme is specific for double-stranded (ds) DNA, and is thus used for selective degradation of ds DNA in complex nucleic acids. DSN depletion is performed prior to library cloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…There is also an increase in the gene discovery rate in a normalized cDNA library, enhancing the identification and analysis of rare transcripts (Cheung et al, 2006). Several normalization methods are reviewed in Bogdanova et al (2009) but duplex-specific nuclease (DSN) normalization (Zhulidov et al, 2004) has been widely used in recent years. (b) Analysis of RNA with an Agilent 2100 Bioanalyzer (Agilent Technologies) using a pooled RNA sample and the same sample after ribosomal RNA (rRNA) depletion with RiboMinus RNA-seq kit (Invitrogen).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…There is also an increase in the gene discovery rate in a normalized cDNA library, enhancing the identification and analysis of rare transcripts (Cheung et al, 2006). Several normalization methods are reviewed in Bogdanova et al (2009) but duplex-specific nuclease (DSN) normalization (Zhulidov et al, 2004) has been widely used in recent years. (b) Analysis of RNA with an Agilent 2100 Bioanalyzer (Agilent Technologies) using a pooled RNA sample and the same sample after ribosomal RNA (rRNA) depletion with RiboMinus RNA-seq kit (Invitrogen).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…The hybridization conditions used in the normalization protocol were the same as those used for cDNA normalization, and allow effective hybridization of sequences that are substantially identical. It has previously been shown that cDNA sequences with 87% sequence identity do not cross-hybridize under these conditions (23). Thus, the sequences representing divergent repetitive elements behave as unique sequences under the hybridization conditions used.…”
Section: Resultsmentioning
confidence: 99%
“…In the model experiment, we used a commercially available Cot-1 fraction of human DNA; however, the driver can be prepared from the cloned DNA population of undesired sequences, as described in Bogdanova et al (23). …”
Section: Resultsmentioning
confidence: 99%
“…Email: endeldw @ uc.edu DNA has also been applied for many techniques using short RNA sequences [16,[18][19][20][21][22][23][24][25][26][27][28][29], but applications for long RNA targets have remained elusive.…”
Section: * Corresponding Authormentioning
confidence: 99%